Efficacy of Psychoeducation and Cognitive Rehabilitation After Mild Traumatic Brain Injury for Preventing Post-concussional Syndrome in Individuals With High Risk of Poor Prognosis: A Randomized Clinical Trial - Caplain, Sophie; Chenuc, Gaelle; Blancho, Sophie; Marque, Sébastien; Aghakhani, Nozar (Frontiers in Neurology, 2019)
Unfavorable outcomes (UO) occur in 15–20% of patients with mild traumatic brain injury (mTBI). Early identification of patients at risk of UO is crucial for suitable management to be initiated, increasing the chances of full recovery. We previously developed a prognostic tool for early identification (8–21 days after the injury) of patients likely to develop UO. Patients whose initial risk factors indicate UO are at risk of developing post-concussion syndrome (PCS). In the present study, we examined the beneficial effects of early multidimensional management (MM) on prognosis. We used our prognostic tool to classify 221 mTBI patients into a UO (97) group or a favorable outcome (FO) group (124). We randomized the UO patients into two subgroups: a group that underwent MM (involving psychoeducation and cognitive rehabilitation) (34) and a control group with no specific treatment other than psychoeducation (46). At 6 months, these two groups were compared to assess the impact of MM. Among the followed-up patients initially classified as having FO (101), 95% had FO at 6 months and only five had PCS [as defined by the Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV classification]. Among the followed-up MM patients, 94% did not have PCS 6 months after injury, whereas 52% of the control patients had PCS. The effect of MM on the recovery of patients at 6 months, once adjusted for the main confounding factors, was significant (p < 0.001). These results show that the initiation of MM after early identification of at-risk mTBI patients can considerably improve their outcomes. Clinical Trials Registration: The study was registered at ClinicalTrials.gov (NCT03811626).